Temporal origin of nitrogen in the grain of tropical wet-season rice - Sheehy, J.E.; Mnzava, M.; Cassman, K.G.; Mitchell, P.L.; Ferrer, A.B.; Robles, R.P.; Pablico, P. (Wiley, 2005)
The total N in the grain is the integral of the product of the total N absorbed at any instant and the fraction of that N eventually allocated to the grain. We investigated the temporal origin of N in the grain of a wet season rice crop and tested the suitability of 15N nitrate (NH4 15NO3) as a label for that purpose. The total N content of rice (Oryza sativa L.) plants was measured by growth analysis throughout the duration of the crop and the measurements were used to calculate the rate of total N uptake. A point‐placement technique was used to deliver small amounts of 15N nitrate to roots of the rice plant and this enabled the eventual fate of the total N absorbed at any time to be determined. The rate at which N was acquired by the panicle exceeded that by the whole plant at 64 d after transplanting (DAT); thereafter, N was transferred from the leaves to the panicle. About 60% of N in the grain was acquired before panicle initiation and was transferred from leaves during grain filling. A comparison between the uptake and retention of labeled nitrate and urea applied separately at 35 DAT showed that 21 and 58% of the 15N nitrate and 15N urea, respectively, were recovered. There were no advantages of using 15N nitrate as opposed to 15N urea as a label in such research of irrigated rice.